ANALISIS PERUANALYSIS OF SHORELINE CHANGES USING THE DIGITAL SHORELINE ANALYSIS SYSTEM (DSAS) METHOD ON RUPAT ISLAND, BENGKALIS BAHAN GARIS PANTAI MENGGUNAKAN METODE DIGITAL SHORELINE ANALYSIS SYSTEM (DSAS) DI PULAU RUPAT KABUPATEN BENGKALIS PROVINSI RIAU - Salsabila, Fatihah; Syarief, Azhari (JURNAL BUANA, 2025)
Rupat Island is one of Indonesia's outermost regions and is administratively part of Bengkalis Regency, Riau Province. Rupat Island has a beach that is being developed as a marine tourism area due to its beautiful white sandy shores. However, with the characteristics of this beach, there is a possibility of changes in the shoreline that will impact various beach uses. To determine the changes in the shoreline, an analysis is conducted using Geographic Information Systems (GIS) with the Digital Shoreline Analysis System (DSAS) method. Based on the analysis from 2002 to 2023, there have been changes in the shoreline due to negative erosion and positive accretion. The total value of all segments for the change distance is 590.16 meters and -629.43 meters, with a change rate of 28.16 meters per year and -30.03 meters per year. The dominant change in the shoreline on the shores of Rupat Island is erosion. This corresponds to field observations in areas such as the Teluk Rhu Beach Lighthouse and Tanjung Lapin Beach in North Rupat District, which are located in segment 1 and show damage to barriers and roads around the beach. The primary factors causing or contributing to changes in the shoreline are more related to hydro-oceanographyrather than anthropogenic factors (social activities).